The Effects of Macroeconomic Factors and Malaysian and Vietnamese Stock Indices on the Jakarta Composite Index - Athaya, Mahadiva Frylia; Kaluge, David (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study aims to examine the influence of macroeconomic factors (inflation, interest rates, and exchange rates), as well as regional stock indices KLCI (Malaysia) and VNI (Vietnam) on the movement of the Composite Stock Price Index (IHSG) in Indonesia. The background of this research stems from the limitations of previous studies, which tended to focus on domestic factors without considering stock market integration within the ASEAN region. This research adopts a quantitative approach using monthly secondary data from 2020 to 2023, analyzed through the Error Correction Model (ECM) to identify both short-term and long-term effects. The results show that in the long run, inflation, interest rates, and VNI have a positive and significant influence on the IHSG dynamics, with varying degrees of influence depending on the time horizon. The implications of this research highlight the importance of considering regional economic integration in investment strategies and policy making in Indonesia’s capital market.